Minireview: The Neuroendocrinology of the Suprachiasmatic Nucleus as a Conductor of Body Time in Mammals - Karatsoreos, Ilia N. (2007)
Circadian rhythms in physiology and behavior are regulated by a master clock resident in the suprachiasmatic nucleus (SCN) of the hypothalamus, and dysfunctions in the circadian system can lead to serious health effects. This paper reviews the organization of the SCN as the brain clock, how it regulates gonadal hormone secretion, and how androgens modulate aspects of circadian behavior known to be regulated by the SCN. We show that androgen receptors are restricted to a core SCN region that receives photic input as well as afferents from arousal systems in the brain. We suggest that androgens modulate circadian behavior directly via actions on the SCN and that both androgens and estrogens modulate circadian rhythms through an indirect route, by affecting overall activity and arousal levels. Thus, this system has multiple levels of regulation; the SCN regulates circadian rhythms in gonadal hormone secretion, and hormones feed back to influence SCN functions.